(untitled) (Revista Brasileira de Contabilidade e Gestão, 2025)
Objective: was to assess the quality of disclosure, the representativeness of recognized goodwill, and the impairment tests conducted in Brazilian public companies. Method: Based on data from Economatica, 33 companies with recognized goodwill on their Balance Sheet as of 31/12/2022 were identified, which constituted the sample for this study. For the analysis of the disclosure level, two checklists were developed based on the applicable standards related to goodwill and its impairment tests. Results: reveal that no company fully complied with all disclosure requirements of CPC 15 (R1) and CPC 01 (R1). Regarding significance, goodwill was found to be the most representative component within the intangible asset group, particularly in the chemical sector. The disclosure of goodwill impairment tests was low among the sample, especially in the construction sector. In terms of the quality of goodwill disclosure, most items on the checklist were classified as "Deficient," and no item received the classification of "Excellent." Contributions: the results highlight the ongoing complexity of goodwill and the deficiencies in the disclosure of its impairment tests, suggesting that regulatory advances have not yet been sufficient to bridge all gaps in transparency and information disclosure related to this asset.